2010
DOI: 10.1155/2010/106461
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Heat Transfer Enhancements: A Review Report

Abstract: Different heat transfer enhancers are reviewed. They are (a) fins and microfins, (b) porous media, (c) large particles suspensions, (d) nanofluids, (e) phase-change devices, (f) flexible seals, (g) flexible complex seals, (h) vortex generators, (i) protrusions, and (j) ultra high thermal conductivity composite materials. Most of heat transfer augmentation methods presented in the literature that assists fins and microfins in enhancing heat transfer are reviewed. Among these are using joint-fins, fin roots, fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 156 publications
0
41
0
Order By: Relevance
“…A very general review on advances in heat transfer enhancements was performed by Siddique et al [3]. They addressed most usual heat transfer enhancers: fins and microfins, porous media, large particles suspensions, nanofluids, phase-change devices, flexible seals, flexible complex seals, vortex generators, protrusions, and ultra-high thermal conductivity composite materials.…”
Section: Other Selective Complementary Sourcesmentioning
confidence: 99%
“…A very general review on advances in heat transfer enhancements was performed by Siddique et al [3]. They addressed most usual heat transfer enhancers: fins and microfins, porous media, large particles suspensions, nanofluids, phase-change devices, flexible seals, flexible complex seals, vortex generators, protrusions, and ultra-high thermal conductivity composite materials.…”
Section: Other Selective Complementary Sourcesmentioning
confidence: 99%
“…(4), (7) and (8), the entransy dissipation rate of the k p vein is (10) According to eqs. (9) and (10), the entransy dissipation rate of the whole elemental leaf-like fin is…”
Section: Constructal Optimization Of the Elemental Leaf-like Finmentioning
confidence: 99%
“…Henceforth, many scholars had done plenty of researches on the fin heat transfer problems [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] based on constructal theory. Bejan and Dan [10] used the analytical method and finite element method to carry out constructal optimization of a tree-shaped fin, and the results showed that the results obtained based on these two methods agreed with each other.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive report on recent advances in heat transfer enhancements was presented by Siddique et al (2010), while the classification of heat transfer enhancement techniques was documented by Bergles (1998). The mechanisms of enhancing heat transfer that require external power, dubbed active methods, comprise, for example, application of stirring in the fluid vessels or surface vibration, as presented by Nesis et al (1994).…”
Section: Introductionmentioning
confidence: 99%